2006
DOI: 10.1200/jco.2005.03.7333
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Comparison of German MLH1 and MSH2 Mutation Carriers Clinically Affected With Lynch Syndrome: A Report by the German HNPCC Consortium

Abstract: The proportion of rectal cancers and shorter time span to metachronous cancers indicates the need for a defined treatment strategy for primary rectal cancers in hereditary nonpolyposis colorectal cancer patients. Male MLH1 mutation carriers require earlier colonoscopy beginning at age 20 years. We propose regular gastric surveillance starting at age 35 years, regardless of the familial occurrence of this cancer. The association of prostate cancer with MSH2 mutations should be taken into consideration both for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
2
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 46 publications
4
86
2
8
Order By: Relevance
“…[1][2][3] Mutations in one of four mismatch repair genes: MLH1, MSH2, MSH6, and PMS2 cause LS and studies suggest that there may be differences in cancer risks for mutation carriers depending on the gene that is mutated. 4,5 Most recent valid estimates of cancer risks to age 70 suggest that individuals with LS have an increased risk of colorectal cancer (22-74%), endometrial cancer (32-42%), and a number of other cancers (such as those of the stomach, ovary, small intestine, biliary tract, and urinary tract). [6][7][8][9] However, previous studies did not often include PMS2 analysis and therefore little is known about the cancer risks for PMS2 monoallelic mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Mutations in one of four mismatch repair genes: MLH1, MSH2, MSH6, and PMS2 cause LS and studies suggest that there may be differences in cancer risks for mutation carriers depending on the gene that is mutated. 4,5 Most recent valid estimates of cancer risks to age 70 suggest that individuals with LS have an increased risk of colorectal cancer (22-74%), endometrial cancer (32-42%), and a number of other cancers (such as those of the stomach, ovary, small intestine, biliary tract, and urinary tract). [6][7][8][9] However, previous studies did not often include PMS2 analysis and therefore little is known about the cancer risks for PMS2 monoallelic mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The median age of disease onset (AO) of MLH1 and MSH2 mutation carriers is 40 and 43 years, respectively, with a wide range of AO. 9 MSH6 contributes to about 15% of all MMR gene mutations in HNPCC. The median AO in MSH6 mutation carriers is 51 years, thus, 10 years older than in MLH1 and MSH2 mutation carriers, also with a wide variation in AO.…”
Section: Introductionmentioning
confidence: 99%
“…21 A recent study published by the German HNPCC consortium, found a correlation between prostate cancers and MSH2 mutation carriers, leading them to propose that this should be taken into consideration during clinical and genetic counseling of MSH2 mutation carriers. 22 In summary, the systematic characterization of this complex mutation in MSH2 using in vitro methods, followed by bioinformatic analysis has shed light on the complex molecular mechanisms underlying MMR gene mutations. The analysis of tumors from this kindred also highlights the challenges of using either IHC or MSI analysis alone, as an indicator of an underlying MMR gene defect.…”
Section: Discussionmentioning
confidence: 99%